1976
DOI: 10.1002/ijc.2910170102
|View full text |Cite
|
Sign up to set email alerts
|

Epstein‐barr virus‐specific IgA serum antibodies as an outstanding feature of nasopharyngeal carcinoma

Abstract: Stimulated by a report on elevated IgA levels in nasopharyngeal carcinoma (NPC), we tested a total of 372 sera from patients with NPC, other carcinomas of head and neck or elsewhere, Burkitt's lymphoma (BL), infectious mononucleosis (IM) or healthy controls. The sera were titrated in indirect immunofluorescence tests for IgA antibodies to Epstein-Barr virus (EBV) capsid antigen (VCA) and to the diffuse (D) or restricted (R) components of the EBV-induced early antigen (EA) complex. The results proved NPC to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
325
4
8

Year Published

1977
1977
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 586 publications
(349 citation statements)
references
References 20 publications
12
325
4
8
Order By: Relevance
“…48 Early recognition of disease onset remains an important factor in survival, as the majority of cases are at an advanced stage upon diagnosis. One of the hallmarks of NPC is the association with EBV (12,13). While the mechanism by which EBV contributes to the initiation or progression of NPC is still not understood, numerous studies have focused on using EBV as a biomarker for recognition, and even therapy, of NPC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…48 Early recognition of disease onset remains an important factor in survival, as the majority of cases are at an advanced stage upon diagnosis. One of the hallmarks of NPC is the association with EBV (12,13). While the mechanism by which EBV contributes to the initiation or progression of NPC is still not understood, numerous studies have focused on using EBV as a biomarker for recognition, and even therapy, of NPC.…”
Section: Discussionmentioning
confidence: 99%
“…11,12 It is notable that EBV is rarely detected in noncancerous epithelial cells, even in the areas adjacent to NPC. 13 EBV is thus an excellent biomarker for NPC diagnosis.…”
mentioning
confidence: 99%
“…These reactivities are detected less frequently and occur at lower titres in sera from patients with Burkitt's lymphoma (BL) and infectious mononucleosis (IM). Both BL and IM, like NPC, are closely associated with EBV, such that all 3 groups of patients have comparably high titres of IgG antibodies against VCA (Henle and Henle, 1976). Moreover, EBV is a ubiquitous virus, such that all the healthy Chinese subjects which served as one of the control groups in our previous studies had serum IgG antibodies against VCA, but none had detectable IgA antibodies .…”
mentioning
confidence: 86%
“…Serum IgA concentration was found to be significantly higher in NPC patients than in control subjects (Wara et al, 1975;Ho et al, 1976). Henle and Henle (1976) reported that NPC patients have high titres of IgA antibody against viral capsid antigen (VCA) (Henle and Henle, 1966) and early antigens (EA) (Henle et al, 1970). These reactivities are detected less frequently and occur at lower titres in sera from patients with Burkitt's lymphoma (BL) and infectious mononucleosis (IM).…”
mentioning
confidence: 99%
“…It was rapidly shown thereafter that NPC patients had elevated titres of IgG antibodies to EBV viral capsid antigen (VCA) and to the diffuse (D) component of the early-antigen (EA) complex (Henle et al, 1970(Henle et al, , 1971(Henle et al, , 1977. IgA antibodies to these 2 antigens were also often demonstrable in sera from NPC patients (Henle & Henle, 1976;Henle et al, 1977). This pattern of elevated IgG and IgA antibodies to VCA and EA (D) has been found uniformly in NPC patients, whether from low-or high-risk areas (Henle & Henle, 1976;Henle et al, 1977;de The et al, 1978;Klein, 1979;Lanier et al, 1981).…”
Section: The Epstein-barr Virus (Ebv) Was Originally Detected In Cultmentioning
confidence: 99%